Hubungan Pola Komunikasi Keluarga Dengan Adiksi Media Sosial Pada Remaja - Afifah, Wardah; Sari, Niken Yuniar; Nopriadi, Nopriadi (JUKEJ : Jurnal Kesehatan Jompa, 2024)
Social media addiction is a global issue and has become a prevalent habit, especially among teenagers. Social media addiction can be observed through the communication patterns in families. The aim of this study is to determine the relationship between family communication patterns and social media addiction in adolescents. This study employs a descriptive correlational design with a cross-sectional approach. The sample consists of 250 respondents selected through stratified random sampling. The measurement tools used are the Revised Family Communication Pattern questionnaire for family communication patterns and the Bergen Social Media Addiction Scale for social media addiction. Data analysis was conducted using the chi-square test. Result: the majority of respondents have a family communication pattern by conversation orientation, totaling 154 respondents (61.6%). The majority of respondents in social media addiction variable are at the allert level, totaling 135 respondents (54%). Statistical test results show a significant relationship between family communication patterns and social media adiksiion in adolescents (p value 0.00 < α 0.05). Conclusion Family communication patterns have a meaningful relationship with social media adiction. Therefore, families need to give special attention to their communication patterns with their children, as the impact significantly influences the character development of adolescents.